Flamenco as an educational tool in the academic curriculum: Strengthening the sense of community and Andalusian identity - Heredia-Carroza, Jesús; López-Ruiz, Carmen; Carrosa-Zayas, Ángeles; Chavarría-Ortiz, Carlos; Palma-Martos, Luis Antonio (Culture and Local Governance / Culture et gouvernance locale, 2025)
This study examines future teachers’ perceptions of incorporating flamenco into the Andalusian educational curriculum and its potential impact on fostering a sense of community and Andalusian identity. The study analysed 301 surveys conducted among university students enrolled in academic education programs. Descriptive statistical analysis revealed that 88.4% of participants supported the integration of formal flamenco in schools. A more detailed analysis of the responses revealed recognition of the influence of flamenco on various aspects such as the preservation of heritage (5.29), a sense of belonging to a community (5.15) and cultural identity (5.17), which guarantees a lasting source of inspiration and growth for future generations. Flamenco is not only considered a cultural relic but a vital part of Andalusia's heritage, essential to its future.